NARRATIVE POLICY ANALYSIS : TRADE OFF PELAYANAN DAN PENGAWASAN DI ERA POST BORDER - Apriansyah, Tofa; Purwadianto, Agus; Hanita, Margaretha (Politeknik Keuangan Negara STAN, 2020)
ABSTRACT:The XV Economic Policy Package has created a gap between control tasks and ease of doing business. This study aims to determine the narrative differences in the implementation of The XV Economic Policy Package, especially in simplifying the import trade system and analyzing strategic changes in the business process of Drug and Food Control. The Narrative Policy Analysis (NPA) is used in this study to analyze at the meso (group/organization) level using interviews with Indonesian-FDA and DGCE Officers. The study is focusing on the narrative of the President of the Republic of Indonesia and the response of the Indonesian-FDA and DGCE Officers who play roles in implementing the controls. Metanaration that appears as a solution analysis is